2022
DOI: 10.1093/jipm/pmac023
|View full text |Cite
|
Sign up to set email alerts
|

Solid Stems and Beyond: Challenges and Future Directions of Resistance to Wheat Stem Sawfly (Hymenoptera: Cephidae)

Abstract: In North America, the wheat stem sawfly (Cephus cinctus Norton) (WSS) is considered a key pest of wheat, causing significant damage to spring and winter wheat. Yield losses from WSS can be due to stem boring and/or stem cutting which causes plants to lodge. Cultural, chemical, and biological management strategies have not effectively controlled WSS. When available, host plant resistance (HPR) is an effective and environmentally friendly approach for pest management and is particularly important for controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…The genetic architecture of stem solidness appears oligogenic, with large effect loci being the main contributors to solidness (Peirce, Cockrell, Mason, et al, 2022). One gene found responsible for solidness is Sst1 (Nilsen et al, 2017(Nilsen et al, , 2020, which was first identified in a quantitative trait locus (QTL) mapping study conducted by Cook et al (2004) on the long arm of wheat chromosome 3B (Qss.msub-3BL).…”
Section: Core Ideasmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic architecture of stem solidness appears oligogenic, with large effect loci being the main contributors to solidness (Peirce, Cockrell, Mason, et al, 2022). One gene found responsible for solidness is Sst1 (Nilsen et al, 2017(Nilsen et al, , 2020, which was first identified in a quantitative trait locus (QTL) mapping study conducted by Cook et al (2004) on the long arm of wheat chromosome 3B (Qss.msub-3BL).…”
Section: Core Ideasmentioning
confidence: 99%
“…Solid‐stem varieties of wheat have been available since the mid‐20th century (Peirce, Cockrell, Mason, et al., 2022; Weiss & Morrill, 1992). In solid‐stem varieties, undifferentiated parenchyma cells create a solid pith within the stem (Berzonsky et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat stem sawfly (WSS), Cephus cinctus (Hymenoptera: Cephidae) is a native, grass‐feeding insect and one of the most important insect pests of wheat in North America 1–3 . WSS has a univoltine life cycle, with adults that emerge in spring and lay eggs within host stems 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Solid-stem varieties of wheat have been available since the mid-twentieth century (Peirce, Cockrell, Mason, et al, 2022;Weiss & Morrill, 1992). In solid-stem varieties, undifferentiated parenchyma cells create a solid pith within the stem (Berzonsky et al, 2003) and this lessens the severity of yield losses in wheat plants (Beres et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In solid-stem varieties, undifferentiated parenchyma cells create a solid pith within the stem (Berzonsky et al, 2003) and this lessens the severity of yield losses in wheat plants (Beres et al, 2007). The genetic architecture of stem solidness appears oligogenic, with large effect loci being the main contributors to solidness (Peirce, Cockrell, Mason, et al, 2022). One gene found responsible for solidness is Sst1 (Nilsen et al, 2020(Nilsen et al, , 2017, which was first identified in a QTL study conducted by Cook et al (2004) on the long arm of wheat chromosome 3B (Qss.msub-3BL).…”
Section: Introductionmentioning
confidence: 99%